Guideline-Based Strategies in the Surgical Treatment of Female Urinary Incontinence: The New Gold Standard is Almost the Same as the Old One - Viereck, V.; Bader, W.; Lobodasch, K.; Pauli, F.; Bentler, R.; Kölbl, H. (Geburtshilfe und Frauenheilkunde, 2016)
The modern sling procedures for treating female stress urinary incontinence encompass numerous methods, materials and manufacturers. On the basis of the current S2e guidelines, the methods used most frequently in the diagnosis of and therapy for stress urinary incontinence in women are critically illustrated. An individualised procedure is necessary for the choice of the surgical method, especially in the presence of accompanying pathologies. This article is intended to help the treating physician to carry out quality-assured diagnostics and therapy for the patient and to offer the best possible urogynaecological management. In addition to the complications and chances of success of the surgical options, the legal aspects of therapy planning are also taken into consideration.
Keywords: stress urinary incontinence; bulking agents; colposuspension; retropubic tape; transobturator tape